Future Trends in Outsourced Marketing Within Division I Intercollegiate Athletics: An Initial Round of a Delphi Study - Robert H. Zullo (Journal of Applied Sports Management, 2013)
The purpose of this study was to examine opinions regarding future trends in outsourced intercollegiate sports marketing from managers of the outsourced marketing companies hired to administer media and marketing rights at select National Collegiate Athletic Association (NCAA) Division I schools. Twenty-eight of the 61 companies selected to participate in this study responded. Via the Delphi Method, data were collected as descriptive statistics, and frequencies were analyzed along with qualitative responses. The findings indicated that outsourced companies seek new business opportunities for the future with athletic departments. The most likely area involved athletic facility naming rights; retailing, licensing and concessions are less desired areas. The responders also indicated that companies are satisfied with their relationship with the schools though properties are looking for means to reduce expenses in the partnership. Those responding also indicated that future ventures and continuous sales efforts are likely to focus on select Division I schools (both private and public) and their respective conferences, since these appear to be the most capable of demonstrating a larger financial return on investment within intercollegiate athletics.
Keywords: Outsourced marketing; sports marketing; intercollegiate athletics; trends; NCAA; Division I; football bowl subdivision; football championship subdivision; sponsorships; corporate sponsors